Chitosan hydrogel with powerful antibacterial and silver release delaying functions and preparation method thereof

Through the reaction of alkynylated chitosan with silver nitrate and the combination of eight-arm PEG crosslinking agent, a chitosan hydrogel with delayed silver release and strong antibacteriality is formed, which solves the problem of silver release in existing silver-based antibacterial materials. Control and toxicity problems have achieved long-acting antibacterial and adaptive healing effects.

CN119241869APending Publication Date: 2025-01-03ZHONGNAN HOSPITAL OF WUHAN UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411283773.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing silver-based antibacterial materials have problems such as uncontrolled silver release and high concentration of silver being toxic to the human body, making it difficult to achieve long-term antibacterial effects.

Method used

Alkynylized chitosan and silver nitrate react to form alkynyl silver nanoparticles, and an eight-arm PEG crosslinking agent is used to form a crosslinking network in the hydrogel, delaying the release of silver and achieving controllable silver release.

Benefits of technology

It achieves an effective silver release effect of up to 7 days, provides strong antibacterial properties and good mechanical properties, and is suitable for nanomedicine fields and adapts to different wound scenarios and shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241869A_ABST
    Figure CN119241869A_ABST
Patent Text Reader

Abstract

The invention relates to chitosan hydrogel with powerful antibacterial and silver release delaying functions and a preparation method of the chitosan hydrogel. The preparation method specifically comprises the following steps: modifying chitosan by using 4-acetylenevaleric acid to prepare alkynylated chitosan (CC-CS), and reducing silver nitrate into silver nanoparticles (AgNPs) and alkynyl silver (C is equivalent to CAg) by utilizing the reduction effect of the chitosan and reacting with the alkynyl silver to obtain the silver-loaded chitosan (Ag-CS). The chitosan hydrogel with the functions of effectively resisting bacteria and delaying silver release is prepared through a Schiff alkali reaction of Ag-CS and a cross-linking agent POSS-PEG-CHO (Polyhedral Oligomeric Silsesquioxane-Polyethylene Glycol-CHO). The chitosan hydrogel provided by the invention has the advantages of uniform pore structure, slow release of silver, strong antibacterial effect and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical auxiliary technology, and in particular to a chitosan hydrogel with strong antibacterial and silver-release delaying functions and a preparation method thereof. Background Art

[0002] Hydrogel is a gel with a three-dimensional cross-linked network formed by natural or synthetic materials through a physical or chemical cross-linking process. The hydrophilic groups on the polymer and its cross-linked structure can accommodate a large amount of water and show good softness and swelling in aqueous media. The water content of hydrogel can reach 99%, which makes the material very friendly to the human body and the water-rich biological environment. Therefore, the application of hydrogel in the field of biomedical materials is of great significance. It can be used as a precursor of other biomedical materials for treatment, such as dressings, drug controlled release carriers, nose, face repair materials, artificial cartilage, etc.; hydrogel has been widely used in tissue engineering, drug delivery, environmental engineering, chemical industry, pharmaceutical engineering and other fields.

[0003] Chitosan is deacetylated chitosan, scientific name polyglucosamine, chemical name (1,4) poly-2-amino-2-deoxy-3-D-glucan, which is a straight-chain polymer compound connected by 3-1,4-glycosidic bonds to N-acetyl-D-glucosamine monomers. Chitosan is a biodegradable material that can be absorbed in the body. A large number of clinical experimental studies have shown that chitosan has special functions such as non-toxicity, non-irritation, good biocompatibility, biodegradability, and no allergic reactions and infections, and can promote the formation of normal fibrin and epithelial tissue. In addition, chitosan also has the properties of easy molding, film formation, anti-coagulation, promotion of wound healing, and antiseptic and antibacterial properties. Therefore, it can be used in medical fields such as artificial skin, surgical sutures, and wound dressing.

[0004] Silver (Ag) has long been used as an antimicrobial agent in the biomedical field. It is well known for its broad-spectrum antimicrobial activity, with strong efficacy against many bacterial, fungal, and viral strains, and little risk of inducing drug resistance. Although many silver-based nanomaterials have been developed in the past decade, there are still unresolved challenges for silver-based antimicrobial materials: 1) uncontrolled silver release does not ensure long-term antimicrobial efficacy; 2) high concentrations of silver can be toxic to the human body. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a chitosan hydrogel with strong antibacterial and delayed silver release functions and a preparation method thereof in view of the above shortcomings.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The preparation method of chitosan hydrogel with strong antibacterial and delayed silver release function comprises the following steps:

[0008] Step 1, using 4-alkyne pentanoic acid to modify chitosan to obtain alkynyl chitosan;

[0009] Step 2, dissolving the acetylated chitosan in deionized water, adding a silver nitrate solution, stirring and reacting under heating conditions, and then dialyzing in water to obtain an Ag-CS solution;

[0010] Step 3: Mix the eight-arm PEG crosslinker solution with the Ag-CS solution to obtain a prepolymer solution, and place the prepolymer solution in a biochemical incubator for gelation to obtain a hydrogel.

[0011] Furthermore, in step 2, the Ag concentration in the Ag-CS solution is 0.1-10 mmol / L.

[0012] Furthermore, in step 3, the molar ratio of the functional group -NH2 in Ag-CS to the functional group -CHO in the eight-arm PEG cross-linking agent is 2-5:1.

[0013] Furthermore, in step 3, the reaction temperature is 25-40° C., and the cross-linking time is 0-30 min.

[0014] Furthermore, in step 3, the solid content of the hydrogel is 5-15%.

[0015] Further, in step 3, the preparation method of the eight-arm PEG cross-linking agent comprises the following steps:

[0016] Step 3.1, dehydrating and condensing trimercaptopropyltrimethoxysilane to generate POSS-8SH;

[0017] Step 3.2, under ultraviolet light, POSS-8SH and allyl polyethylene glycol are mixed and reacted to generate POSS-PEG-OH;

[0018] Step 3.3, POSS-PEG-OH is mixed with p-formylbenzoic acid to undergo an esterification reaction, and the OH end of PEG is modified to CHO to obtain an eight-arm PEG crosslinker POSS-PEG-CHO.

[0019] The chitosan hydrogel with strong antibacterial and delayed silver release functions is prepared by the method.

[0020] The beneficial effects of the present invention are:

[0021] The present invention delays the release of silver through the reversible conversion of alkynyl silver and the polymer network of chitosan through the reduction and loading effect of chitosan, making it controllable. Alkynyl chitosan reduces silver ions to silver nanoparticles and alkynyl silver and then loads them into hydrogel. The cyclic reversible reaction of alkynyl silver and the three-dimensional porous structure of hydrogel can achieve an effective silver release effect of up to 7 days, so it can be well applied to the field of nanomedicine. The present invention utilizes the characteristics of chitosan's reducibility, the reversible conversion of alkynyl silver and the strong antibacterial property of silver to prepare a chitosan hydrogel with strong antibacterial and delayed silver release functions. The cross-linking system formed by Schiff base makes the hydrogel have self-healing and injectable functions, and can adapt to different wound scenes and shapes. The chitosan hydrogel provided by the present invention has the advantages of uniform pore structure, fast gelation and good mechanical properties, good silver sustained release effect, and strong antibacterial effect on common bacteria.

[0022] The present invention is described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The schematic diagram of the synthesis of the silver-loaded chitosan of the present invention;

[0024] Figure 2 This is a scanning electron microscope test image of the chitosan hydrogel provided in the embodiment of the present invention;

[0025] Figure 3 A photoelectron spectrum test diagram of silver in chitosan hydrogel provided in an embodiment of the present invention;

[0026] Figure 4 The ultraviolet spectrum of silver in the chitosan hydrogel provided in the embodiment of the present invention;

[0027] Figure 5 The release diagram of silver in the chitosan hydrogel provided in the embodiment of the present invention;

[0028] Figure 6 The distribution diagram of each element in the chitosan hydrogel provided in the embodiment of the present invention;

[0029] Figure 7 This is an antibacterial graph of the chitosan hydrogel provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following examples are provided for a better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.

[0031] like Figure 1As shown, the method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions of the present invention comprises the following steps:

[0032] Step (1), synthesizing alkynyl chitosan, 4-alkyne pentanoic acid (2.29 g, 11.95 mmol), EDCI (2.29 g, 11.95 mmol) and NHS (1.37 g, 11.95 mmol) were added to deionized water and stirred for 20 min to activate the carboxyl group of 4-alkyne pentanoic acid. Next, chitosan (0.5 g, 2.99 mmol) was dispersed in a 1% w / v HCl solution until it was completely dissolved. Then, the activated 4-alkyne pentanoic acid was added dropwise to the chitosan solution and stirred at room temperature for 48 h. The reaction solution was dialyzed for 7 days through a 14000 Da cutoff dialysis membrane, and the dialyzed solution was freeze-dried to obtain the final product, i.e., CC-CS.

[0033] Step (2), preparing chitosan (Ag-CS) loaded with silver nanoparticles and alkynyl silver, first dissolving CC-CS in deionized water, and then slowly adding a certain amount of silver nitrate solution. The mixture was stirred at 80°C for 12 hours, and then dialyzed in water. The obtained Ag-CS sample was stored in a refrigerator for further experiments.

[0034] Step (3), synthesizing an eight-arm PEG crosslinker (POSS-PEG-CHO), first, through the dehydration condensation of trimercaptopropyltrimethoxysilane, POSS-8SH is generated; secondly, under ultraviolet light irradiation, POSS-8SH and allyl polyethylene glycol (Allyl-PEG-OH) undergo a photo "click" reaction to generate POSS-PEG-OH; finally, through the esterification reaction of POSS-PEG-OH with p-formylbenzoic acid, the OH end of PEG is modified to CHO to obtain POSS-PEG-CHO.

[0035] Step (4), dissolving the POSS-PEG-CHO prepared in step (3) in a fixed volume of ultrapure water, ultrasonically treating until completely dissolved, and mixing with the Ag-CS solution prepared in step (2), and then placing the prepolymer solution in a biochemical incubator at 37° C. for gelation to obtain a hydrogel, wherein in step (4), the reaction temperature is 25-40° C., the crosslinking time is 0-30 min, and the molar ratio of the functional group -NH2 in Ag-CS to the functional group -CHO in POSS-PEG-CHO is 2-5:1. The solid content of the hydrogel is 5-15%.

[0036] In the step (2), the Ag concentration is 0.1-10 mmol / L, wherein the Ag concentration in Example 1 is 1 mmol / L, the Ag concentration in Example 2 is 2.5 mmol / L, the Ag concentration in Example 3 is 5 mmol / L, and the Ag concentration in the comparative example is 0 mmol / L.

[0037] Allyl polyethylene glycol (Allyl-PEG-OH) in each example is a commercially available product (provided by Beijing Jiankai Technology Co., Ltd.) with a molecular weight of 2.5 kDa.

[0038] In each example, chitosan is a commercially available product (provided by Titan Technology Co., Ltd.) with a molecular weight of 300,000 Da and a degree of deacetylation of 90%.

[0039] The eight-arm PEG crosslinker (POSS-PEG-CHO) in each embodiment is a product synthesized independently in the laboratory and characterized by various test methods. The average molecular weight of POSS-PEG-CHO in the present invention is 17000Da.

[0040] The parameters in Examples 1-3 of the present invention and the comparative examples are shown in Table 1 below:

[0041] Table 1

[0042]

[0043] Scanning electron microscopy Figure 2 As shown, the chitosan hydrogels provided by the present invention all have a porous sponge-like structure, and their pore sizes are uniform, with an average pore size between 100 and 200 μm, and have a large porosity.

[0044] Photoelectron spectroscopy of silver in hydrogel

[0045] Taking Example 3 as an example, the element valence distribution of Ag in the hydrogel was characterized. The hydrogel of Example 3 was prepared. After sufficient swelling, the hydrogel was placed in an oven to obtain a thin slice, which was cut into 5 mm × 5 mm × 1 mm (length × width × thickness) square slices. The Thermo Escalab 250Xi instrument was used, using a monochromatic aluminum X-ray photoelectron spectroscopy source (X-ray energy 1486.6 eV, test spot area 500 μm, X-ray tube voltage 15 KV, current 10 mA, analysis chamber vacuum 2 × 10 -9 mbar) was used to characterize the elemental valence state distribution of Ag in the hydrogel.

[0046] like Figure 3As shown in the XPS test of Example 3, the 3d orbital of Ag appears at 370 eV. In the fine spectrum of Ag3d, two peaks are observed at 368.3 and 372.1 eV, which are the characteristics of the presence of AgNPs. In addition, the peak at 367.6 eV is Ag + These results indicate that the presence of Ag in the hydrogel + and AgNPs.

[0047] UV spectroscopy test of silver in hydrogel

[0048] Using ultrapure water as the background, the hydrogels of Examples 1, 2, 3 and the comparative example were immersed in ultrapure water to swell for 3 days, and the supernatant was aspirated to measure the absorbance of the solution in the wavelength range of 300-700 nm using a UV-visible spectrophotometer.

[0049] like Figure 4 As shown in the figure, compared with the comparative example, the embodiment presents a maximum absorption peak at about 420nm, and the absorption wavelength is in the range of 380-450nm. As the Ag concentration increases, the absorbance also increases accordingly.

[0050] Silver release testing from hydrogels

[0051] The four samples of Example 1, 2, 3 and the comparative hydrogel were immersed in a PBS solution (15 mL) and shaken at 37°C (100 rpm). When the preset interval was reached, the hydrogel was taken out and the PBS solution was placed in a refrigerator for testing. Finally, the release amount of AgNPs was measured by inductively coupled plasma atomic emission spectroscopy (ICP).

[0052] like Figure 5 As shown, the hydrogels of Examples 1, 2, and 3 showed Ag + The release amounts were 16.3%, 17.8%, and 20.1%, respectively. + The release amounts were 48.2%, 51.3%, and 53.4% ​​respectively within 6 days. + The release amounts were 85.6%, 91.6%, and 94.3%, respectively. The release rates of the hydrogels in the three embodiments slowed down significantly, and the release equilibrium state was basically reached after 7 days. + The release rate showed an increasing trend.

[0053] Distribution test of elements in hydrogel

[0054] Taking the hydrogel of Example 3 as an example, the microscopic morphology and element distribution of the hydrogel were characterized. The hydrogel of Example 3 was prepared, immersed in a PBS (pH 7.4, 10 mM) solution for 12 h, and then freeze-dried at -50°C. The microscopic morphology and element distribution of the hydrogel were scanned using a SIGMA500 field emission scanning electron microscope (FE-SEM) equipped with an XFlash6|30 energy dispersive spectrometer (EDS).

[0055] like Figure 6 As shown, the results showed that carbon (C), nitrogen (N), oxygen (O), silicon (Si) and silver (Ag) elements existed in the hydrogel and Ag was evenly distributed in the hydrogel system.

[0056] Antibacterial testing of hydrogels

[0057] S. aureus (Gram-positive bacteria) and E. coil (Gram-negative bacteria) were used as experimental subjects, and the antibacterial properties of the hydrogel provided by the present invention were evaluated using the plate count method. Specifically, the bacterial suspension (2×10 8 CFU / ml, 100 μL) were incubated with PBS (negative control group), double antibody group (positive control group) and hydrogel group at 37°C for 20 min. After incubation, the mixture was evenly spread on LB agar plates (diluted 1×10 4 After incubation at 37°C for 24 h, the number of bacterial colonies was counted and recorded to evaluate the antibacterial effect.

[0058] like Figure 7 As shown, compared with the control group and the comparative example, the embodiment shows excellent antibacterial effect. The comparative example group shows 70% and 73% antibacterial effect on the two bacteria, respectively, which is attributed to the inherent antibacterial activity of chitosan. In addition, the hydrogel with high silver concentration shows even better antibacterial effect. The antibacterial rates of Examples 1, 2, and 3 on the two bacteria reached 41% and 44%, 72% and 81%, 89% and 95%, respectively, far exceeding the control group and the comparative example.

[0059] The above results show that the chitosan hydrogel provided by the present invention has the advantages of uniform pore structure and good mechanical properties; the chitosan hydrogel provided by the present invention can achieve a good silver sustained release effect through the reversible conversion of alkynyl silver and the network structure of the hydrogel, and has excellent antibacterial effects on S. aureus and E. coil. It has the properties of providing a moist environment, sterilization, silver sustained release, etc. that are not available in the traditional method, and can improve the rate of wound healing.

[0060] The above is an example of the best implementation of the present invention, and the parts not described in detail are common knowledge of ordinary technicians in the field. The protection scope of the present invention shall be based on the content of the claims, and any equivalent transformation based on the technical enlightenment of the present invention is also within the protection scope of the present invention.

Claims

1. A method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions, characterized in that: The following steps are involved: Step 1, using 4-alkyne pentanoic acid to modify chitosan to obtain alkynyl chitosan; Step 2, dissolving the acetylated chitosan in deionized water, adding a silver nitrate solution, stirring and reacting under heating conditions, and then dialyzing in water to obtain an Ag-CS solution; Step 3: Mix the eight-arm PEG crosslinker solution with the Ag-CS solution to obtain a prepolymer solution, and place the prepolymer solution in a biochemical incubator for gelation to obtain a hydrogel.

2. The method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions according to claim 1, characterized in that: In the step 2, the Ag concentration in the Ag-CS solution is 0.1-10 mmol / L.

3. The method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions according to claim 1, characterized in that: In the step 3, the molar ratio of the functional group -NH2 in Ag-CS to the functional group -CHO in the eight-arm PEG cross-linking agent is 2-5:

1.

4. The method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions according to claim 1, characterized in that: In the step 3, the reaction temperature is 25-40° C., and the cross-linking time is 0-30 min.

5. The method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions according to claim 1, characterized in that: In the step 3, the solid content of the hydrogel is 5-15%.

6. The method for preparing chitosan hydrogel with strong antibacterial and delayed silver release functions according to claim 1, characterized in that: In step 3, the preparation method of the eight-arm PEG cross-linking agent comprises the following steps: Step 3.1, dehydrating and condensing trimercaptopropyltrimethoxysilane to generate POSS-8SH; Step 3.2, under ultraviolet light, POSS-8SH and allyl polyethylene glycol are mixed and reacted to generate POSS-PEG-OH; Step 3.3, POSS-PEG-OH is mixed with p-formylbenzoic acid to undergo an esterification reaction, and the OH end of PEG is modified to CHO to obtain an eight-arm PEG crosslinker POSS-PEG-CHO.

7. Chitosan hydrogel with strong antibacterial and delayed silver release function, characterized in that: Prepared by the method according to any one of claims 1 to 6.

Citation Information

Cited By

  • Acellular porcine pericardium and POSS-PEG-CHO cross-linked biological nano composite material as well as preparation method and application thereof

    CN120022427A

  • Gel compositions and related methods

    WO2026192856A1